Expression of p53 Protein Product in Triple Negative Breast Cancers and Relation with Clinical and Histopathological Parameters - Jasar, Dzengis; Smichkoska, Snezhana; Kubelka, Katerina; Filipovski, Vanja; Petrushevska, Gordana (Walter de Gruyter GmbH/Macedonian Academy of Sciences and Arts, 2015)
AbstractIntroduction: "Triple" negative breast cancer is a subgroup of so-called basal-like breast cancer. They are represented with 15% of all breast cancers, characterized with lack of hormone receptor as well as with negative expression of HER2 test. These tumors are more frequent in Afro-Americans and Latin-Americans, in patients with BRCA1 mutations and in patients with recent delivery. The aim of this study is to present the immunohistochemical and clinico-pathological characteristics of the triple negative breast cancer and their correlation with expression of the protein product of the tumor suppressor gene p53.Methods: A retrospective analyses of 24 patients with triple negative breast cancer was performed. All of the patients were evaluated in the Histopathological Laboratory of the Clinical Hospital Sistina, during the period from June 2009, until June 2011. The standard immunohistochemical procedures, including the hormone receptor status, HER2 status, proliferative index - Ki67 and p53 gene protein product were performed, as well as additional immunohistochemical staining for socalled basal keratins (Cytokeratin 5/6 and high molecular weight cytokeratin 34BE12).Results: The age of the patients ranged from 29-77 years. Positive lymph nodes were found in 14 (59%) patients. The tumor was poorly differentiated in 19 patients (79%). Overexpression of the p53 protein product was evaluated in 19 (79%) of the cases. All p53 negative patients (5/5) had poorly differentiated tumors (G3), associated with positive regional lymph nodes. The p53 positive group expressed quite opposite correlation, only 9/19 (47%) were with positive lymph nodes (p = 0.03). The expression of p53 protein product was also associated with the nuclear grade (p = 0.005), the mitotic index (p = 0.001), lymph-vascular invasion (p = 0.005) and with the proliferation index Ki67 (p = 0.003). There was a trend for association with the tumor size - pT (p = 0.05).Conclusion: According to the results, the triple negative breast cancers are subgroup of the poorly differentiated neoplasms frequently associated in the younger age groups. The majority of these have overexpression of the p53 protein product, which in other hand, are inversely correlated with lymph nodes metastases. Hence, the necessity of enriching the immunohistochemical protocol of these patients with new antibodies, in order to evaluate their expression, which would be helpful for prediction the outcome of different therapeutical modalities.
Keywords: breast cancer; p53 gene; histopathology; oncology